Multifunctional polyether ester fiber composite film and preparation method and application thereof
By depositing a mixed solution of MXene and sodium chloride on a polyether ester fiber membrane, the contradiction between conductivity and stretchability in flexible wearable devices is resolved, achieving a balance between high conductivity and stretchability, and possessing excellent sensing, heating, and antibacterial properties, thereby improving the overall performance and safety of the device.
Patent Information
- Application Number
- CN202511606438.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-05
- Publication Date
- 2026-05-15
- Estimated Expiration
- 2045-11-05
AI Technical Summary
Existing fiber-based conductive materials for flexible wearable electronic devices present a challenge in balancing conductivity and stretchability, and are also prone to bacterial growth with long-term use, affecting health and performance.
A mixed solution of MXene and sodium chloride was deposited on a polyether ester fiber membrane substrate using a combination of electrospinning and vacuum filtration to form a multifunctional composite membrane. Sodium ions were used to enhance the spreading and connection of MXene nanosheets, forming a stable conductive network.
It achieves a good balance between high conductivity and stretchability, and has excellent strain sensing performance, Joule heating performance and photothermal antibacterial performance, which improves the overall performance and safety of the equipment.
Smart Images

Figure CN121065943B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a multifunctional polyether ester fiber composite membrane, its preparation method, and its application, belonging to the field of biomedical material preparation technology in the chemical aspect of bandages, dressings, absorbent pads, or surgical supplies. Background Technology
[0002] Currently, flexible wearable electronic devices are a type of surgical instrument, showing great promise in fields such as health monitoring, human-computer interaction, and smart healthcare. This has created an urgent need for advanced materials that combine excellent flexibility, conductivity, and multifunctional integration. Among these, fiber-based conductive materials have become a research hotspot due to their lightweight structure, good breathability, and ease of integration with the human body or fabrics. Ideal flexible conductive materials not only need to possess high elasticity and high conductivity to achieve stable monitoring of human movement, but should also integrate additional functions such as Joule heating and photothermal antibacterial properties to expand their applications in intelligent protection and treatment.
[0003] Polyether ester fibers, with their unique physical and chemical properties, have become one of the ideal carrier materials for wearable devices. These fibers possess excellent elasticity, which not only maintains the stability of the fabric structure but also significantly improves the sensitivity of the device. However, polyether esters, as traditional polymer materials, are inherently non-conductive, thus requiring modification to impart conductivity. MXenes (such as Ti3C2T) are one such modification method. x Polyether ester fibers (PEFs), as a new type of two-dimensional inorganic material, have attracted much attention due to their extremely high metallic conductivity, abundant surface functional groups, and excellent photothermal conversion efficiency. They are often used as functional fillers to impart electrical and photothermal properties to polymer matrices. Currently, achieving low-cost, mass-producible, and stable functional modification of PEFs still faces significant challenges.
[0004] In practical applications, fiber-based conductive materials still face numerous challenges. For instance, the inherent physical contradiction between rigid conductive materials and flexible, stretchable matrices presents a challenge in balancing conductivity and stretchability. Furthermore, conductive fibers are prone to bacterial growth during long-term use, potentially causing skin allergies or infections. This not only affects user health but also leads to the accumulation of bacterial metabolites on the fiber surface, forming biofouling that further impairs conductivity and mechanical properties, and reduces user experience. Therefore, developing flexible fiber materials that combine high conductivity, sensing capabilities, and good antibacterial properties is crucial for improving the overall performance and safety of wearable devices. Summary of the Invention
[0005] This invention provides a multifunctional polyether ester fiber composite membrane, its preparation method, and its application, which can effectively solve the above-mentioned problems.
[0006] A multifunctional polyether ester fiber composite membrane, comprising:
[0007] A polyether ester (TPEE) fiber membrane substrate; and a functional coating deposited on the surface of the polyether ester (TPEE) fiber membrane substrate, the functional coating comprising MXene and sodium chloride (NaCl).
[0008] In some embodiments, the MXene is Ti3C2T x .
[0009] A method for preparing the aforementioned multifunctional polyether ester fiber composite membrane includes the following steps:
[0010] S1: Polyether ester (TPEE) fiber membrane prepared by electrospinning;
[0011] S2: Mix the MXene aqueous dispersion with sodium chloride (NaCl) to obtain a NaCl / MXene mixed aqueous solution;
[0012] S3: The NaCl / MXene mixed aqueous solution is deposited on the surface of the TPEE fiber membrane by vacuum filtration;
[0013] S4: Dry the deposited fiber membrane to obtain the multifunctional polyether ester fiber composite membrane.
[0014] In some embodiments, in step S1, polyether ester particles are dissolved in hexafluoroisopropanol (HFIP) to obtain a polyether ester spinning solution with a concentration of 4-6 wt%; the electrospinning conditions include: a voltage of 20-30 kV, a flow rate of 15-25 µL / min, and a roller speed of 250-350 rpm.
[0015] In some embodiments, the MXene aqueous dispersion in step S2 is prepared by the following steps: Ti3AlC2 powder is added to a mixed solution of hydrochloric acid and lithium fluoride, and the mixture is stirred at 38-42°C for 45-50 h; the reaction product is then subjected to centrifugal washing, ultrasonic exfoliation, and centrifugation in sequence, and the supernatant is collected to obtain Ti3C2T. x MXene aqueous dispersion.
[0016] In some embodiments, in step S2, the concentration of the MXene aqueous dispersion is 3-7 mg / mL.
[0017] In some embodiments, in step S2, the concentration of NaCl in the NaCl / MXene mixed aqueous solution is 0.01 mol / L to 0.05 mol / L.
[0018] In some embodiments, the concentration of NaCl is 0.03 mol / L.
[0019] In some embodiments, the drying temperature in step S4 is 55-65°C.
[0020] A flexible wearable electronic device includes the aforementioned multifunctional polyether ester fiber composite membrane, wherein the multifunctional polyether ester fiber composite membrane is used as at least one of a strain sensor, a Joule heating element, or a photothermal antibacterial layer.
[0021] The beneficial effects of this invention are:
[0022] 1. This invention uses a combination of electrospinning and vacuum filtration to prepare multifunctional polyether ester fiber composite membranes. The process is simple, easy to operate, and low in cost.
[0023] 2. In the preparation process of the multifunctional polyether ester fiber composite membrane of the present invention, NaCl is added to the MXene dispersion. The sodium ions shield the electrostatic forces between the negatively charged MXene sheets, allowing the MXene nanosheets to spread more uniformly during deposition. Simultaneously, sodium ions act as binding sites, enhancing the interconnection between the MXene nanosheets and forming a stable conductive network. That is, MXene and NaCl exert a synergistic effect. At the optimal NaCl concentration of 0.03 mol / L, the TPEE-MXene-NaCl-3 fiber membrane exhibits a conductivity as high as 10.47 S / cm, while maintaining an elongation at break of 516%, achieving a good balance between conductivity and stretchability.
[0024] 3. The multifunctional polyether ester fiber composite membrane obtained by this invention can produce a sensitive and stable resistance response to the bending of human joints (such as fingers and wrists), and the signal is clear and reproducible, proving that it has excellent strain sensing performance.
[0025] 4. The multifunctional polyether ester fiber composite membrane prepared by this invention exhibits excellent Joule heating performance, reaching a temperature of 115.9℃ at 4V; it also possesses excellent photothermal conversion capability, achieving high performance under 808nm NIR laser (1W / cm²) conditions. 2 The temperature under irradiation can reach 154.2℃.
[0026] 5. Based on its excellent photothermal effect, the fiber membrane achieved a 100% sterilization rate against both Escherichia coli and Staphylococcus aureus after 15 minutes of irradiation with an 808nm NIR laser, demonstrating outstanding photothermal antibacterial performance. Attached Figure Description
[0027] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained from these drawings without creative effort.
[0028] Figure 1 This is a schematic diagram of the preparation process of polyether ester fiber in an embodiment of the present invention.
[0029] Figure 2 This is a schematic diagram of the preparation process of MXene dispersion in an embodiment of the present invention.
[0030] Figure 3 This is a schematic diagram of the preparation process of the multifunctional polyether ester fiber composite membrane in an embodiment of the present invention.
[0031] Figure 4 This is a schematic diagram of the mechanism of NaCl-assisted MXene vacuum filtration.
[0032] Figure 5 These are scanning electron microscope (SEM) images of TPEE, TPEE-MXene, and TPEE-MXene-NaCl-3 fiber membranes.
[0033] Figure 6 These are test graphs of the mechanical properties of the multifunctional polyether ester fiber composite membrane, where (a) is the stress-strain curve and (b) is the elongation at break.
[0034] Figure 7 This is a conductivity test chart of a multifunctional polyether ester fiber composite membrane.
[0035] Figure 8 These are test images of the sensing performance of TPEE-MXene-NaCl-3 fiber membrane for monitoring human motion, where (a) represents finger bending and (b) represents wrist bending.
[0036] Figure 9 These are Joule heating performance test images of TPEE-MXene-NaCl-3 fiber membrane. (a) is an infrared image at different voltages, and (b) is a comparison of Joule heating performance with other materials.
[0037] Figure 10The photothermal properties of TPEE-MXene-NaCl fiber membranes containing different concentrations of NaCl are shown: (a) TPEE-MXene; (b) TPEE-MXene-NaCl-1; (c) TPEE-MXene-NaCl-2; (d) TPEE-MXene-NaCl-3; (e) TPEE-MXene-NaCl-4; (f) TPEE-MXene-NaCl-5.
[0038] Figure 11 These are experimental diagrams showing the antibacterial effects of different fiber membranes on Escherichia coli and Staphylococcus aureus under 808 nm NIR irradiation.
[0039] Figure 12 This is a biocompatibility diagram of TPEE, TPEE-MXene, and TPEE-MXene-NaCl-3 fiber membranes. Detailed Implementation
[0040] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention.
[0041] In this embodiment of the invention, TPEE-MXene-NaCl-1, TPEE-MXene-NaCl-2, TPEE-MXene-NaCl-3, TPEE-MXene-NaCl-4, and TPEE-MXene-NaCl-5 fiber membranes are respectively prepared by using mixed aqueous solutions containing 0.01 mol / L, 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, and 0.05 mol / L NaCl.
[0042] Example 1: Preparation of multifunctional polyether ester fiber composite membrane
[0043] (1) Preparation of polyether ester (TPEE) fibers, such as Figure 1As shown, 0.798 g of polyether ester particles were added to 10 mL of hexafluoroisopropanol (HFIP) and stirred at room temperature until the polyether ester particles were completely dissolved, yielding a polyether ester spinning solution with a concentration of 5 wt%. Electrospinning was performed with the injection pump flow rate set at 20 µL / min, the high-voltage power supply voltage at 27 kV, and the roller receiver rotation speed at 300 rpm. Electrospinning was carried out for 4 hours, and polyether ester nanofiber membranes (TPEE nanofiber membranes) were collected on the roller.
[0044] (2)MXene(Ti3C2T x Preparation of aqueous dispersions as follows Figure 2 As shown, 3.2 g of lithium fluoride was added to a polytetrafluoroethylene container containing 40 mL of 9 M hydrochloric acid and stirred for 15 min to dissolve it. Then, 2 g of Ti3AlC2 was added, and the mixture was stirred at 40 °C for 48 h. After the reaction, the reaction solution was washed three times by centrifugation with 2 M hydrochloric acid, and then washed again by centrifugation with deionized water. Each centrifugation was performed at 3500 rpm for 1 min until the supernatant was black. Subsequently, sonication was performed in an ice-water bath under an argon atmosphere for 15 min. After sonication, the dispersion was centrifuged again at 3500 rpm for 30 min, and the supernatant was collected to obtain a monolayer of Ti3C2T. x MXene aqueous dispersion. Monolayer MXene powder can be obtained by freeze-drying.
[0045] (3) Preparation of conductive polyether ester fiber membranes, as follows Figure 3As shown, 20 mL of an MXene aqueous dispersion with a concentration of 5 mg / mL was prepared. Different masses of NaCl were added to the 20 mL of the 5 mg / mL MXene aqueous dispersion to prepare NaCl / MXene aqueous solutions with NaCl concentrations of 0.01 mol / L, 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, and 0.05 mol / L. These NaCl / MXene aqueous solutions of different concentrations were deposited onto the surface of the polyether ester fiber membrane prepared in step (1) by vacuum filtration. The deposited fiber membranes were dried at 60 °C to obtain TPEE-MXene-NaCl-1, TPEE-MXene-NaCl-2, TPEE-MXene-NaCl-3, TPEE-MXene-NaCl-4, and TPEE-MXene-NaCl-5 fiber membranes (Composite Fiber Membrance).
[0046] Comparative Example 1
[0047] Preparation of TPEE-MXene fiber membrane: Prepare 20 mL of 5 mg / mL MXene aqueous dispersion (without NaCl), and deposit it on the surface of the polyether ester fiber membrane prepared in step (1) of Example 1 by vacuum filtration to obtain TPEE-MXene fiber membrane.
[0048] Comparative Example 2
[0049] TPEE fiber membrane: The pure TPEE fiber membrane prepared in step (1) of Example 1 was used as a blank control.
[0050] Test Example: Performance Characterization and Analysis
[0051] (1) Mechanism and morphology analysis, such as Figure 4 The diagram illustrates the mechanism of NaCl-assisted MXene vacuum filtration. When NaCl is mixed with an MXene dispersion (containing unprocessed MXene sheets), sodium ions aggregate around the negatively charged MXene nanosheets, shielding some of the negative charge between the sheets and weakening the electrostatic forces between them. This allows the MXene sheets to spread more uniformly during deposition onto the TPEE fiber membrane surface. At a moderate sodium ion concentration... + The adsorption effect is enhanced, with metal ions acting as adsorption sites to bind to MXene nanosheets. This, combined with gravity, causes the nanosheets to stack horizontally, exhibiting a horizontal orientation. When the metal ion concentration is excessive (Excess Na...), the adsorption effect is enhanced.+ Adsorption is the dominant process, and metal ions severely disrupt the electrostatic balance of the MXene solution, leading to significant aggregation of nanosheets.
[0052] like Figure 5 The scanning electron microscope images shown clearly demonstrate the structure of the TPEE fiber membranes. The surfaces of the TPEE-MXene and TPEE-MXene-NaCl-3 fiber membranes are completely coated with MXene, and wrinkles are formed on the surface of the fiber membranes due to the introduction of MXene and NaCl.
[0053] (2) Mechanical performance testing, such as Figure 6 As shown in Figures (a) and (b), the mechanical properties of the composite fiber membrane were tested. (a) shows the stress-strain curve, and (b) shows the elongation at break. Pure TPEE fiber membranes exhibit high tensile strength. When MXene is deposited onto the surface of a flexible TPEE fiber membrane (TPEE-MXene), stress concentration easily occurs at the interface between the rigid nanosheets and the flexible substrate, leading to a decrease in the elongation at break of the TPEE-MXene fiber membrane. Adding NaCl (TPEE-MXene-NaCl-1) results in an interaction with the functional groups on the surfaces of TPEE and MXene, further restricting chain segment movement and further decreasing the elongation at break. However, as the NaCl concentration increases to 0.02 mol / L (TPEE-MXene-NaCl-2), the elongation at break increases slightly, then remains around 500%. The elongation at break of TPEE-MXene-NaCl-3 (0.03 mol / L NaCl) is 516%.
[0054] (3) Conductivity testing was performed using a four-probe resistivity meter to measure the conductivity σ of the fiber membrane. For example... Figure 7 As shown, the conductivity initially increases and then decreases with increasing NaCl concentration. The highest conductivity, 10.47 S / cm, is observed in TPEE-MXene-NaCl-3 at a NaCl concentration of 0.03 mol / L. This increase in conductivity is attributed to the strong binding energy between sodium ions and the -OH groups on the MXene nanosheets. The metal ions act as binding sites, enhancing the interconnections between the MXene nanosheets and inducing the formation of a stable conductive network. When the NaCl concentration is too high (e.g., 0.04 and 0.05 mol / L), excess sodium ions and Cl- are present in the system. - Ions hinder the transport of electrons between MXene sheets, resulting in a decrease in conductivity.
[0055] (4) Sensing performance testing: A TPEE-MXene-NaCl-3 fiber membrane (elongation at break 516%, conductivity 10.47 S / cm) was selected for subsequent testing. Resistance changes were recorded using a source meter. For example... Figure 8 As shown in Figures 8(a) and 8(b), when the test subject bends their fingers (30°, 60°, 90°) and wrists, the rate of change of resistance ((R-R0) / R0) of the TPEE-MXene-NaCl-3 fiber membrane increases with the increase of the bending angle, forming a clear and reproducible waveform signal, proving its excellent sensing performance.
[0056] (5) Joule heating performance test, as follows Figure 9 As shown in Figure (a), voltages ranging from 0V to 4V were applied to the TPEE-MXene-NaCl-3 fiber membrane. The temperature of the fiber membrane varied significantly under different voltages: 28.7℃ at 0V, 32.4℃ at 1V, 49.2℃ at 2V, 79.7℃ at 3V, and 115.9℃ at 4V. This indicates that the fiber membrane is highly sensitive to the input voltage. Figure 9 As shown in (b), this fiber membrane exhibits superior Joule heating performance compared to materials reported in other literature.
[0057] (6) Photothermal performance testing: TPEE-MXene-NaCl fiber membranes containing different concentrations of NaCl were irradiated with 808 nm near-infrared light of different powers for 120 s, and the temperature changes of the samples were recorded using an infrared imager. For example... Figure 10 As shown, as the laser power increases from 0.25 W / cm 2 Increase to 1 W / cm 2The maximum temperature of TPEE-MXene-NaCl fiber membranes containing different concentrations of NaCl showed a gradual increasing trend. This is because MXene has strong near-infrared absorption properties. When exposed to 808 nm near-infrared light, the MXene component in the fiber membrane effectively absorbs photons of this specific wavelength, leading to electron excitation and the conversion of light energy into heat, resulting in a temperature increase. As shown in Table 1, with the increase of NaCl content, the maximum temperature of the TPEE-MXene-NaCl fiber membrane under laser irradiation of the same power first increases and then decreases. This is because the introduction of NaCl allows MXene to be deposited more uniformly on the surface of the TPEE fiber membrane, forming a continuous and dense thermally conductive network, thereby achieving the ability to quickly absorb light energy and convert it into heat. However, excessive NaCl causes MXene agglomeration, making it difficult to deposit on the TPEE fiber membrane during vacuum filtration, resulting in a decrease in the MXene content on the fiber membrane surface and a decline in the ability to absorb light energy and convert it into heat. The results indicate that the TPEE-MXene-NaCl-3 fiber membrane has the best photothermal performance.
[0058] Table 1. Maximum temperatures of TPEE-MXene-NaCl fiber membranes containing different NaCl concentrations under different laser powers.
[0059]
[0060] (7) Photothermal antibacterial performance test: Escherichia coli and Staphylococcus aureus were used to investigate the photothermal antibacterial performance of the fiber membrane. Bacterial culture medium was heated at 37 ℃ and 150 r·min. -1 The culture was incubated in a constant-temperature shaker for 24 h. The culture was then diluted to 10⁻⁶ with culture medium. 5 Add 15 mg of TPEE, TPEE-MXene, and TPEE-MXene-NaCl to the bacterial culture, respectively, and then use an 808 nm NIR laser (power 1 W / cm²) to perform the reaction. 2 Irradiate the bacteria for 15 minutes. After irradiation, place the bacterial culture at 37 °C and 150 r·min. -1 Continue culturing in a constant-temperature shaker for 30 min. Spread 100 μL of the bacterial culture onto an agar plate, repeating the process three times, and incubate at 37 ℃ for 24 h. Observe bacterial growth and count colonies. Results are as follows: Figure 11As shown, the antibacterial effect of TPEE fiber membranes was not significant under 808 nm NIR laser irradiation. The bacterial survival rate in the TPEE-MXene group was significantly reduced, indicating that the addition of MXene significantly improved the antibacterial performance of the composite fiber membrane. No colonies grew on plates of TPEE-MXene-NaCl fiber membranes with different concentrations of NaCl, achieving 100% antibacterial effect. This is because under 808 nm NIR laser irradiation, the TPEE-MXene-NaCl fiber membrane rapidly converts light energy into heat, reaching a temperature of 125 °C. When bacteria are exposed to this heat, their cell membrane structure is damaged, and their DNA suffers irreversible damage, directly leading to bacterial death. Furthermore, MXene generates reactive oxygen species (ROS) under NIR laser irradiation. ROS can penetrate the cell membrane and react with organic matter within the bacteria, leading to bacterial death.
[0061] (8) Biocompatibility test of TPEE-MXene-NaCl-3 fiber membrane: CCK-8 method was used to detect cytotoxicity. Figure 12 The results showed that the cell viability of TPEE-MXene and TPEE-MXene-NaCl-3 fiber membranes was not significantly different from that of pure TPEE, and the different concentrations of fiber membranes had little effect on cell viability, which remained above 95%, indicating that all groups of cells maintained high viability and no obvious biotoxicity was observed. The TPEE-MXene-NaCl-3 fiber membrane had the highest cell viability, demonstrating its good biocompatibility. This is because MXene aggregation slightly affects cell activity, while the introduction of NaCl promotes a more uniform distribution of MXene on the fiber surface and neutralizes the negative charge of MXene, better mimicking the natural extracellular matrix and thus enhancing cell proliferation.
[0062] In summary, the multifunctional flexible fiber membrane prepared by this invention combines advantages such as simple preparation process, low cost, superior stretchability, excellent conductivity and sensing properties, outstanding Joule heating performance, and photothermal antibacterial properties. The multifunctional flexible fiber membrane prepared by this invention can be widely used in smart textiles and wearable devices.
[0063] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A multifunctional polyether ester fiber composite membrane, characterized in that, include: Polyether ester fiber membrane substrate prepared by electrospinning; And a functional coating deposited on the surface of the polyether ester fiber membrane substrate by a vacuum filtration method, the functional coating comprising MXene and sodium chloride; The functional coating is formed by depositing a NaCl / MXene mixed aqueous solution obtained by mixing MXene aqueous dispersion with sodium chloride, wherein the concentration of sodium chloride in the NaCl / MXene mixed aqueous solution is 0.03 mol / L; The MXene is Ti3C2T x .
2. A method for preparing a multifunctional polyether ester fiber composite membrane as described in claim 1, characterized in that, Includes the following steps: S1: Polyether ester fiber membrane prepared by electrospinning; S2: Mix the MXene aqueous dispersion with sodium chloride to obtain a NaCl / MXene mixed aqueous solution; the concentration of sodium chloride in the NaCl / MXene mixed aqueous solution is 0.03 mol / L; S3: The NaCl / MXene mixed aqueous solution is deposited on the surface of the polyether ester fiber membrane by vacuum filtration; S4: Dry the deposited fiber membrane to obtain the multifunctional polyether ester fiber composite membrane.
3. The preparation method according to claim 2, characterized in that, In step S1, polyether ester particles are dissolved in hexafluoroisopropanol to obtain a polyether ester spinning solution with a concentration of 4-6 wt%. The electrospinning conditions include: voltage of 20-30 kV, flow rate of 15-25 µL / min, and roller speed of 250-350 rpm.
4. The preparation method according to claim 2, characterized in that, The MXene aqueous dispersion described in step S2 is prepared by the following steps: Ti3AlC2 powder is added to a mixed solution of hydrochloric acid and lithium fluoride, and the mixture is stirred at 38-42℃ for 45-50 h; the reaction product is then subjected to centrifugal washing, ultrasonic exfoliation, and centrifugation in sequence, and the supernatant is collected to obtain Ti3C2T. x MXene aqueous dispersion.
5. The preparation method according to claim 4, characterized in that, In step S2, the concentration of the MXene aqueous dispersion is 3-7 mg / mL.
6. The preparation method according to claim 2, characterized in that, In step S4, the drying temperature is 55-65℃.
7. A flexible wearable electronic device, characterized in that, The multifunctional polyether ester fiber composite membrane as described in claim 1 is used as at least one of a strain sensor, a Joule heating element, or a photothermal antibacterial layer.
